2007
DOI: 10.1073/pnas.0707484104
|View full text |Cite
|
Sign up to set email alerts
|

Fragile X mental retardation protein deficiency leads to excessive mGluR5-dependent internalization of AMPA receptors

Abstract: Fragile X syndrome (FXS), a common inherited form of mental retardation, is caused by the functional absence of the fragile X mental retardation protein (FMRP), an RNA-binding protein that regulates the translation of specific mRNAs at synapses. Altered synaptic plasticity has been described in a mouse FXS model. However, the mechanism by which the loss of FMRP alters synaptic function, and subsequently causes the mental impairment, is unknown. Here, in cultured hippocampal neurons, we used siRNAs against Fmr1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
170
2
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(190 citation statements)
references
References 38 publications
17
170
2
1
Order By: Relevance
“…Since spine shape is correlated with the number of AMPA receptors in the postsynaptic density (Matsuzaki et al, 2001), these data correlate with the rescue effect of MPEP on AMPA receptor trafficking as shown by Nakamoto et al (Nakamoto et al, 2007). In the latter study, the concentrations of MPEP used on primary neurons (10-50 μM) differed from our experiments due to different time courses of the experiments.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…Since spine shape is correlated with the number of AMPA receptors in the postsynaptic density (Matsuzaki et al, 2001), these data correlate with the rescue effect of MPEP on AMPA receptor trafficking as shown by Nakamoto et al (Nakamoto et al, 2007). In the latter study, the concentrations of MPEP used on primary neurons (10-50 μM) differed from our experiments due to different time courses of the experiments.…”
Section: Discussioncontrasting
confidence: 52%
“…The mGluR theory states that AMPA receptor internalization triggered by mGluR5 stimulation (Snyder et al, 2001), is exaggerated in Fmr1 KO mice, accounting for the enhanced hippocampal LTD found in knockout mice (Bear et al, 2004;Huber et al, 2002). Recently it was shown that FMRP deficient dendrites indeed show aberrant AMPA receptor trafficking resulting in a significantly reduced number of AMPA receptors at the plasma membrane (Nakamoto et al, 2007). Moreover, Fmr1 KO mice that are crossbred with mice that have a 50% reduction in mGluR5 expression were shown to be rescued in several phenotypic aspects (Dolen et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…This mechanism appears to be compromised in FXS, because reduced levels of FMRP were shown to lead to increased mGlu 5 -mediated GluA endocytosis in rat hippocampal neurons (Nakamoto et al, 2007). The mGlu 1/5 -dependent translational induction of two FMRP targets, Arc/Arg3.1 and MAP1B, which were suggested to be involved in activity-regulated GluA endocytosis in hippocampal neurons (Davidkova and Carroll, 2007;Waung et al, 2008), is absent in Fmr1 KO mice Park et al, 2008).…”
Section: Increased and Protein Synthesis-independent Mglu 1/5 Ltd In Fxsmentioning
confidence: 99%
“…One of the major findings leading to the mGluR theory is that in the hippocampus the group 1 mGluR receptor, mGluR5, is involved in long-term depression (LTD), a form of synaptic plasticity that is enhanced in the Fmr1 knockout (Fmr1 KO) mouse (4,5). The underlying basis for this enhanced hippocampal mGluR-LTD is abnormally high internalization of the AMPA receptor (AMPAR) subunit, GluR1, caused by the absence of the endpoint inhibition normally provided by FMRP (2,6). Interestingly, defective AMPAR-mediated plasticity has also emerged as a common phenotype in other brain areas in the Fmr1 KO mouse, including the cortex and cerebellum (7)(8)(9)(10)(11).…”
mentioning
confidence: 99%